О географической изменчивости Aglenchus agricola de Man, 1884 (Nematode, Tylencnidae) - Сигарева, Д.Д.; Краснопольский, Н.Н. (Вестник зоологии, 1974)
In the statistical processing of data on 13 mophological characters of Aglenchus agricola essential differences are found between geographically separated populations in the body total length, the body length from the anterior end to the anus, in de Man's proportions a, b and V%. The above-mentioned characters are not recommended to be taken as a basis when describing the new species of the genus Aglenchus.